2007
DOI: 10.1063/1.2403841
|View full text |Cite
|
Sign up to set email alerts
|

Very high-cycle fatigue failure in micron-scale polycrystalline silicon films: Effects of environment and surface oxide thickness

Abstract: Fatigue failure in micron-scale polycrystalline silicon structural films, a phenomenon that is not observed in bulk silicon, can severely impact the durability and reliability of microelectromechanical system devices. Despite several studies on the very high-cycle fatigue behavior of these films (up to 1012cycles), there is still an on-going debate on the precise mechanisms involved. We show here that for devices fabricated in the multiuser microelectromechanical system process (MUMPs) foundry and Sandia Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…[11] Another recent study, by Alsem et al [48,49] , confirmed, using HVTEM, the presence of this cyclic stress-assisted oxidation on resonator specimens similar to the ones used by Muhlstein et al (i.e., MUMPs fabricated 2 µm thick polysilicon [44,45] ). Enhanced oxide thicknesses were imaged at the locations of maximum stresses after fatigue cycling, but not in samples that had been monotonically loaded and failed by overload fracture; such reaction layers were also not found after cycling in high vacuum (2 × 10 -5 Pa) ( Figure 14).…”
Section: Figurementioning
confidence: 70%
See 4 more Smart Citations
“…[11] Another recent study, by Alsem et al [48,49] , confirmed, using HVTEM, the presence of this cyclic stress-assisted oxidation on resonator specimens similar to the ones used by Muhlstein et al (i.e., MUMPs fabricated 2 µm thick polysilicon [44,45] ). Enhanced oxide thicknesses were imaged at the locations of maximum stresses after fatigue cycling, but not in samples that had been monotonically loaded and failed by overload fracture; such reaction layers were also not found after cycling in high vacuum (2 × 10 -5 Pa) ( Figure 14).…”
Section: Figurementioning
confidence: 70%
“…First and foremost, the absence of thin-film silicon fatigue failures in high vacuum, and the observed influence of humidity on the fatigue life are strong indications of a significant environmental contribution to cracking ( Figure 5) [19,20,30,31,48,49] . However, observations that the number of cycles to failure is frequency-independent are clear indications of a true fatigue contribution too ( Figure 18) [26,27,55] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations